Comparison of Chemotherapy Combined With Chidamide Versus Chemotherapy in the Frontline Treatment for Peripheral T-Cell Lymphoma - Wang, Jinni; Su, Ning; Fang, Yu; Ma, Shuyun; Zhang, Yuchen; Cai, Jun; Zou, Qihua; Tian, Xiaopeng; Xia, Yi; Liu, Panpan; Li, Zhiming; Huang, He; et al. (Frontiers in Immunology, 2022)
Background: Peripheral T-cell lymphoma (PTCL) is featured with a poor survival outcome. China has approved chidamide, an oral novel histone deacetylase inhibitor, for patients diagnosed with relapsed or refractory PTCL. Objective: We compared the benefit of traditional chemotherapy alone and a combination of chidamide and traditional chemotherapy against newly diagnosed PTCL. Prognostic factors related to progression and survival in patients diagnosed with untreated PTCL were also investigated. Methods: 104 patients with newly diagnosed PTCL were enrolled and divided into chemotherapy (ChT) group and chemotherapy combined with chidamide (ChT+C) group. Survival curves were plotted by the Kaplan-Meier method. Univariate and multivariate analysis were conducted with Log-rank test and Cox’s proportional hazard regression. Subgroup analysis and interaction tests were conducted to evaluate factors associated with prognostic differences between ChT and ChT+C groups. Results: Compared with patients in ChT group, those in ChT+C group had superior progression-free survival (PFS) (p=0.047). However, there was no significantly statistical difference observed between the two groups in overall survival (OS) (p=0.212). High IPI scores have a negative relationship with survival. Multivariate analysis revealed that the type of frontline treatment regimen is an independent factor associated with PFS of PTCL patients (p=0.045). In the subgroup of patients with high international prognostic index scores (3-5), the HR value for PFS comparing ChT with ChT+C was 4.675. A test of interaction between IPI and treatment showed statistical significance (p = 0.037), implying that the benefits of ChT+C are higher for patients with high IPI scores. Conclusions: In summary, the combination of ChT and chidamide may provide a promising prospect for patients with newly diagnosed PTCL.